Preparation of Cellulose Nanocrystals from α-Cellulose and Optimization of its Isolation Conditions - Azar Haghighi Poshtiri (Regional Information Center for Science and Technology (RICeST), 2017)
Cellulose nanocrystals (CNC) are new class of cellulose materials that find wide applications in various research areas over the past two decades. These nanoparticles are usually made by acid hydrolysis of cellulose substances such as wood, cotton, Starch etc. The main aim of this study is to find the optimal conditions for obtaining an aqueous stable colloid suspension of cellulose nanocrystal (CNC) from α-cellulose with a high-yield procedure. Therefore various conditions of acid hydrolysis were evaluated as reaction temperature and reaction time. The percentage of yield was calculated for all suspensions. The morphology of the prepared CNC was characterized by Transmission Electron Microscopy (TEM), Environmental Scanning Electron Microscopy (ESEM) and the crystallinity was measured by X-ray diffraction (XRD). The results showed that highest yield of CNC (88%), was achieved from the reaction condition of 60 minutes at 60 °C. Generally, rod-like shape crystals achieved from α-cellulose with an average size of 35-50 nm and high crystallinity (92%) can be make it to a convenient and competitive source for the production of cellulose nanocrystal for various industries.